Effect of Laser Wavelengths on the Silver Nanoparticles Size Prepared by PLAL - Mohammed J. Haider; Mohammed S. Mahdi (Engineering and Technology Journal, 2016)
In this present study, Pulsed Laser Ablation in Liquid (PLAL) experiment setup for synthesis colloidal solution of silver-NPs. The laser system was used in this study, a (Nd-YAG) nanosecond laser system with optimal pulse duration of 10 ns and repetition rate 1-6 Hz. The Laser wavelengths were: 1064 nm, 532 nm and 355 nm. The spot size of the laser beam on the surface of metal plate was varied in the range of 1.4-1.5 mm in diameter by changing the distance between the focusing lens and the metal plate.The ablation process was typically done for 1 minute. The average particle size has been characterized by TEM, SEM and UV-Vis investigation. From morphologyresults for colloidal silver nanoparticles images were spherical shape and average size of the particles is 55-60 nm at wavelength (λ =1064 nm), average size of the particles is 35-40 nm at(λ =532 nm) and average size of the particles is 28 nm at(λ =355 nm).